2021
DOI: 10.1038/s41598-021-82287-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed CRISPR-Cas9 system in a single adeno-associated virus to simultaneously knock out redundant clock genes

Abstract: The mammalian molecular clock is based on a transcription-translation feedback loop (TTFL) comprising the Period1, 2 (Per1, 2), Cryptochrome1, 2 (Cry1, 2), and Brain and Muscle ARNT-Like 1 (Bmal1) genes. The robustness of the TTFL is attributed to genetic redundancy among some essential clock genes, deterring genetic studies on molecular clocks using genome editing targeting single genes. To manipulate multiple clock genes in a streamlined and efficient manner, we developed a CRISPR-Cas9-based single adeno-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, recent developments in CRISPR genome editing have created new opportunities for generating cell culture models without first generating mutant mice. Several studies including ours demonstrated that clock genes can be knocked out efficiently in culture using CRISPR ( 55 59 ). One key limitation in cell models today is the lack of precise endogenous phase and period reporters working like clock hands other than the mPer2-Luc reporter in MEFs.…”
Section: Discussionmentioning
confidence: 97%
“…However, recent developments in CRISPR genome editing have created new opportunities for generating cell culture models without first generating mutant mice. Several studies including ours demonstrated that clock genes can be knocked out efficiently in culture using CRISPR ( 55 59 ). One key limitation in cell models today is the lack of precise endogenous phase and period reporters working like clock hands other than the mPer2-Luc reporter in MEFs.…”
Section: Discussionmentioning
confidence: 97%
“…Before we initiated the project in mouse models, feasibility of the project was tested in a clock cell model U2OS which has been proven to have a functional clock and to be amenable to CRISPR genome editing 17, 47, 52 . When the motifs harboring W448 in PER1 and W419 in PER2 were targeted by CRISPR, diverse indel mutations were generated including in-frame mutations leading to deletion of several AAs (Fig S2).…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments in genome editing have created new opportunities for generating cell culture models without first generating mutant mice. Several studies including ours demonstrated that clock genes can be knocked out efficiently in culture using CRISPR 17,[44][45][46][47] . To our knowledge, however, there are no HDRmediated mutations made in clock genes in MEFs by CRISPR.…”
Section: Introductionmentioning
confidence: 96%
“…However, recent developments in CRISPR genome editing have created new opportunities for generating cell culture models without rst generating mutant mice. Several studies including ours demonstrated that clock genes can be knocked out e ciently in culture using CRISPR [55][56][57][58][59] . One key limitation in cell models today is the lack of precise endogenous phase and period reporters working like clock hands other than the mPer2-Luc reporter in MEFs.…”
Section: Discussionmentioning
confidence: 96%